IbM MEMBANGUN âDESA CERMATâ MELALUI BIMBINGAN BELAJAR DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Susanti, Vera Dewi; Maharani, Swasti (Jurnal Terapan Abdimas, 2016)
IbM is motivated by the many children who come from poor families who can not follow the lessons, after school activities so that they spend a lot of play. In addition , many students and graduates who do not have the activity / work due to lack of jobs. Therefore, in this IbM the researchers intend to make les. In this IbM focused guidance for poor children and will involve students and graduates IKIP PGRI Madiun. Partner is the chief village IbM Watuompak and Bangunrejo. IbM aims to improve student learning outcomes through tutoring mathematics as a means to build a "Cermat" village in the village Rejosari Kebonsari Madiun and students or graduates to become active through tutoring. The stages of this research starts from the preparation phase support equipment guidance, the next stage of implementation / field, program evaluation by a team of researchers and partners and the final completion of the final report.Keywords: Tutoring , Math Learning Outcomes